Management of Carcinoma of Esophagus in Old Patient with Panchagavya Therapy as a Palliative Care-A Case Report - Punam G. Sawarkar; Damini Raut; Nandini Bhojarj; Gaurav Sawarkar (Journal of Pharmacy and Bioallied Sciences)
Esophageal cancer is a male-dominant, aggressive malignancy with a five-year survival rate of 15%-20%, predominantly affecting developed nations. Esophageal squamous cell carcinoma (ESCC) is the most common subtype. This case study involves a 70-year-old man with ESCC, who was suffering from difficulty swallowing, inability to burp, constant nausea, and occasional trouble swallowing water for two months. He was successfully treated with Panchagavya Chikitsa, which included Panchagavya Ghrita, Gomutra Arka, Kwath of Amla-Yashtimadhu-Shatpushpa, Haritaki Churna, Haridra Ghanvati, and Vibhitaki Avaleha, along with Nasya, Nabhipurana with Panchagavya Ghrita, and Matra Vasti with Tila Taila over six months. Significant symptom improvement was observed, attributed to the Rasayana (rejuvenative), Balya (strengthening), and Jeevaniya (vitality-enhancing) properties of the treatments. These properties inhibit cancer growth, nourish tissues, and restore balance due to their antioxidant effects. Panchagavya formulations showed promising results without adverse effects, highlighting their efficacy in improving the quality of life for this geriatric patient with ESCC.